2019
DOI: 10.1101/655712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing mechanisms of transcription elongation through cell-to-cell variability of RNA polymerase

Abstract: The process of transcription initiation and elongation are primary points of control in the regulation of gene expression. While biochemical studies have uncovered the mechanisms involved in controlling transcription at each step, how these mechanisms manifest in vivo at the level of individual genes is still unclear. Recent experimental advances have enabled single-cell measurements of RNAP molecules engaged in the process of transcribing a gene of interest. In this manuscript, we use Gillespie simulations to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Gene-expression dynamics, whose more natural description is in terms of phenomenological variables such as the rates of production, degradation, binding, and unbinding, is just one example that remains challenging to model without resorting to exhaustive numerical simulations in many cases. Researchers have made some progress by using equilibrium statistical mechanics in which one uses the binding energies of transcription factors to determine steady-state gene-expression levels in microbes [31][32][33][34][35][36][37][38]. The main reason for the success of this approach is that certain processes, such as the binding and unbinding of a transcription factor at a target locus on DNA, occur much faster than the other processes involved in gene expression.…”
Section: Landscapes For Particles and Genes With Slow Changesmentioning
confidence: 99%
“…Gene-expression dynamics, whose more natural description is in terms of phenomenological variables such as the rates of production, degradation, binding, and unbinding, is just one example that remains challenging to model without resorting to exhaustive numerical simulations in many cases. Researchers have made some progress by using equilibrium statistical mechanics in which one uses the binding energies of transcription factors to determine steady-state gene-expression levels in microbes [31][32][33][34][35][36][37][38]. The main reason for the success of this approach is that certain processes, such as the binding and unbinding of a transcription factor at a target locus on DNA, occur much faster than the other processes involved in gene expression.…”
Section: Landscapes For Particles and Genes With Slow Changesmentioning
confidence: 99%
“…control of transcriptional initiation [56] and elongation [57,58], measure translational dynamics [59], and even count molecules [60]. Note that, while appropriate for qualitatively estimating the order of magnitude of bursting timescales, raw fluorescence measurements from MS2 and PP7 experiments such as those in Figure 1A-C do not directly report on the promoter state.…”
Section: Using Bursting Dynamics To Probe Different Models Of Transcr...mentioning
confidence: 99%
“…Depending on the timescales of the initiation and elongation processes, they will affect the polymerase measurements differently. Recent studies [26,47,86,87] explored this interplay of initiation and elongation dynamics in determining polymerase number distribution using numerical simulations. By considering a wide range (1/s to 1/min [81]) of initiation rates for genes in E.coli, it was shown that if the initiation timescales are much longer (one order of magnitude) than the elongation timescales associated with pausing, backtracking etc, the polymerase counts and interpolymerase distances remain largely unaffected by the elongation dynamics, as in the case of most of the mRNA promoters in it E. coli and yeast [81].…”
Section: Limitations Of the Modeling Frameworkmentioning
confidence: 99%
“…By considering a wide range (1/s to 1/min [81]) of initiation rates for genes in E.coli, it was shown that if the initiation timescales are much longer (one order of magnitude) than the elongation timescales associated with pausing, backtracking etc, the polymerase counts and interpolymerase distances remain largely unaffected by the elongation dynamics, as in the case of most of the mRNA promoters in it E. coli and yeast [81]. For genes that are highly transcribed such as the ribosomal genes, the initiation and elongation timescales become comparable, and hence the elongation dynamics can significantly alter the distribution of polymerases on a gene [49,50,86].…”
Section: Limitations Of the Modeling Frameworkmentioning
confidence: 99%